Bearing capacity of a bent pile - Gan, Chin Hwi (2009)
The objective of this dissertation is to study the various parameters that affect the behaviour of a bent pile. This has been achieved by performing a parametric study on a bent pile made up of a two linear segments; i.e. an upper, vertical segment follow by an inclined, lower segment. The bend is deliberately introduced by assuming that the pile is fabricated and installed with an initial kink. The pile in the parametric study is assumed to be a 400 mm diameter prestressed precast concrete spun pile, installed in a uniform clay layer with increasing shear strength over depth.